Penguatan Insentif Lingkungan dan Pendapatan, Aksi Bank Sampah Cangkir Hijau Metro - Yudiyanto Yudiyanto; Era Yudistira; Atika Lusi Tania (Dinamika Lingkungan Indonesia, 2020)
Waste Problem will not cause pollution if it is managed properly.  More over it can provide economic benefit for the community.  The Waste Bank "Cangkir Hijau" has a way to grow its independence and role so as to be able to prove its existance provides economic benefits for community and the preservation of environmental cleanliness.  This Paper discusses the innovation strategy of the role and independence of the Waste Bank ‘Cangkir Hijau’ in realizing environmental cleanliness and economic benefits for the surrounding community.  This research was conducted with descriptive qualitative.  The results of the study incicate the independence and role of the waste bank ‘Cangkir Hijau’ be formed because it is done by applying the principles of social movement and creativity. Including improving managerial skills,  innovation of various types of waste saving, and promoting waste bank, thus providing incentives on additional income for community and creating a cleaner enviornment.